Dilemmas of Civic Society in Lithuania - Laurėnas, Vaidutis (Sociologija. Mintis ir veiksmas, 2003)
The article offers an attempt to reconstruct the concept of civic society and, with the help of new instrumentation, to analyze the dilemmas of the appearance and development of the civic society in Lithuania. In the concept of the civic society, the emphasis on its non-political and self-building character predominates. The basic motive of the attempt to reconstruct the civic society, as presented in the article, accentuates the necessity of the appearance of the political component in the civic society. The political connections of the civic society have been labeled as sub-politics or non-state politics. Not only the potential of the political connections of the civic society, but also their limits have been analyzed: the civic society is able not only to take over some of the state functions that are managed inefficiently, but, by doing it in a resolute way, to stimulate the society’s fragmentation. It has also been emphasized that the concept of the civic society implies two not identical, but simultaneous actions: the civic society is not built by the state “from above”, however, it is not the result of a mere self-building process, either. The dilemmas of political - non-political, system - anti-system, consolidated- fragmentary, local – global characteristics are typical of the appearance and development of the civic society in Lithuania. Beside the universal content of the dilemmas in question, the unique character of their development in Lithuania is quite obvious. Lithuania has not yet managed to escape from the “non-synchronic circle” of the (self)-building of the state and the civic society. The statement that the civic society in Lithuania is arising anew each time after the formation of the national state would be too categorical. However, Lithuania does not have any substantial experience of the non-interrupted co-existence of the civic society and the state, its development has been discrete. The civic society in Lithuania fails to get rid of the anti-system approach with respect to their own country, although anti- system values usually form with regard to foreign states. The lack of synchronism is not favorable to any newly – developing system, and the more effort is made to consolidate the non-political character of the civic society, the less favorable it becomes. The motive of the building of the politicized civic society, of the realization of its political component remains unattractive in Lithuania, as it is identified with the striving of the state to control the society. In fact, one might expect the alienation of the civic society from the state, but not its total de-politicizing. Unless the civic society is politicized, i.e. unless attempts are made to solve certain common problems of the society without the state’s interference or with its minimum interference more and more frequently, the interventionist strivings of the state will never in any way yield to restriction. Thus, the gap between the civic society and the state in Lithuania leaves no serious chance for their interrelation, and simultaneously for their modernization. The present situation results from the contradiction of nationalism and an anti-system approach, which historically is no longer promising. The anti-system approach determines the absence of widely-spread civic movements that would aim to introduce changes in the life of the society, but not merely seek for state power, in Lithuania. The inertia of the anti-system approach caused unjustifiable strivings to de-politicize the civic society and not to collaborate with the state. The anti-system approach is a serious obstacle to the appearance of self-activating, i.e. irretrievably strong, civic society. The rudiments of the civic society in Lithuania experience not so much the necessary support from the state, but rather intensive interventionism. The duty of political democracy with regard to the civic society - to open the possibility for a free individual to set their own goals independently and together with their compatriots to establish one or another type of social order - remains unfulfilled. In its turn, the civic society retains a strict anti-system approach. All that witnesses the weakness of both levels - the state and the civic - of the organization of our society. In such a situation, not only the internal consolidation potential of the Lithuanian civic society, but also its openness for global processes remains problematic. However, with Lithuania becoming integral part of the fast-progressing world, it cannot avoid the new factors that influence the development of the civic society: post-materialism and information, and that can become a weighty argument for the appearance of a “loyal division” between the civic society and the state.